Orstom rewarded - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1989)
The French Academie d'Agriculture has recently awarded its special Jean Dufrenoy Prize to Bernard Dreyfus of ORSTOM for his work on nitrogen fixation. The research on Sesbania rostrata (see SPORE 12), the legume with exceptional nitrogen-fixing...